A Design of Arabic Writing Skills Test for Beginners According to Standardization of the American Council On The Teaching Of Foreign Languages (ACTFL) - Mahmudi, Ihwan; Hasanah, Maghfirotul; Ismail, Moh.; Saifulloh, Ahmad; Fatawi, Izzul (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2024)
Abstract Tests or questions that use ACTFL standards at level Novice is one way to find out Arabic language learning standards and students' ability standards, especially writing skills tests. ACTFL standardization at the Novice level consists of 3 levels, namely Novice High (high beginner level), Novice Mid (intermediate beginner level), and Novice Low (low beginner level). The research uses a qualitative method through a literature study by studying the Skills Guide book American Council On The Teaching Of Foreign Languages (ACTFL) and other literature such as articles and books. Based on the results of the analysis carried out in this research, there are 20 tests or questions according to ACTFL standardization at the level Novice that is 20% of the questions of difficulty level or Novice High (4 questions), 50% of the questions are medium level or Novice Mid (10 questions), and 30% easy level questions or Novice Low (6 questions). Keywords: Test, Writing Skills, Beginner (Novice), ACTFL.